2007
DOI: 10.1177/1466424007073207
|View full text |Cite
|
Sign up to set email alerts
|

Lessons to be learned: a case study approach. Lateral aberrant thyroid tissue: is it always malignant?

Abstract: Traditionally 'lateral aberrant thyroid' tissue present in cervical lymph nodes in the face of a clinically normal thyroid gland is held to be a metastasis from an occult primary thyroid carcinoma. A patient in whom follicular thyroid tissue was found in a lymph node lateral to the carotid sheath in the presence of a thyroid gland which was histologically free of cancer is herewith presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…From 1942 on, it had been believed that the presence of ''lateral aberrant thyroid'' represented metastases of thyroid primary carcinomas [11][12][13]. However, later reports showed the presence of normal thyroid ectopic tissue in these supposed ''aberrant tumors'' [3-10, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1942 on, it had been believed that the presence of ''lateral aberrant thyroid'' represented metastases of thyroid primary carcinomas [11][12][13]. However, later reports showed the presence of normal thyroid ectopic tissue in these supposed ''aberrant tumors'' [3-10, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of submandibular involvement, the therapeutic approach should be based on surgical excision with histopathologic evaluation of the mass [2][3][4][5][6]8]. Although rare, there are cases of neck masses suspected of being ectopic thyroid tissue and later confirmed as metastases of thyroid carcinoma [1][2][3] and also cases where the ectopia may harbor a primary malignant neoplasia [1,2,13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally 'lateral aberrant thyroid' tissue present in cervical lymph nodes in the face of a clinically normal thyroid gland is held to be a metastasis from an occult primary thyroid carcinoma. 1 It is a rare developmental abnormality that involves aberrant embryogenesis of the thyroid gland when it migrates from the floor of the primitive foregut to its final region between the second and fourth tracheal cartilages. The prevalence reported as 1 per 1,00,000-3,00,000 people, rising to 1 per 4,000-8,000 patients having thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
“…Solitary posterior triangle neck mass as the rare sole presentation Irfan Mohamad et al follicular thyroid tissue was found in a lymph node lateral to the carotid sheath in the presence of a thyroid gland which was histologically free of cancer 8 .…”
mentioning
confidence: 99%